Analisis Kualitas Pelayanan Pada Pelayanan Terpadu Satu Pintu (Ptsp) Pengadilan Negeri Bengkulu - Endri Novian; Effed Darta Hadi; Yessy Elita (Student Journal of Business and Management, 2023)
The aim of the research is to find out what the quality of the Bengkulu District Court's one-stop integrated service is and what criteria need to be improved based on priorities. The research approach is qualitative using a questionnaire distributed to selected samples. The method for analyzing the results of distributing questionnaires uses the calculation stages of Service Quality (Servqual), Importance Performance Analysis (IPA), and Potential Gain Customer Value (PGCV). The results of the research show that the perception of service users' expectations of the PTSP of the Bengkulu District Court is in the "Very High" category, namely with a value range of 4.39 - 4.75, while the perception of performance regarding the quality of PTSP services is PTSP. Bengkulu District Court's PTSP service as a whole received a response of "Very Satisfied" with a score range of 4.36 - 4.81. Based on the service quality gap analysis (Gap Analysis), it was found that 37.5% or 12 indicators were in a negative gap, where the physical evidence variable, reliability and guarantee variables each had 3 indicators, the responsiveness variable had 2 indicators and the empathy variable had 1 indicator. Based on the results of the IPA analysis, 7 indicators were found in Quadrant A, 14 indicators in Quadrant B, while in Quadrant C 5 indicators were found, and in Quadrant D 6 indicators were found.